Simulation and Analysis of Dynamics of Lower Limb Exoskeleton Rehabilitation Robots - Ma Xiaojun; Liu Yuyang; Jia Qiusheng; Liu Desheng; Liu Xunbao; Yuan Mingrun (Jixie chuandong)
A lower limb exoskeleton rehabilitation robot can effectively improve the rehabilitation efficiency of patients with impaired lower limb motor function and reduce the workload of rehabilitation physicians. Therefore, a lower limb exoskeleton rehabilitation robot is designed, the relationship between the motion state of the exoskeleton robot and the motion mechanism of each joint is explored, the Lagrange equation to model the dynamics of the lower limb exoskeleton is used and the established virtual prototype model into Adams for dynamic simulation is imported. Further, the torque changes of each joint of the lower limb exoskeleton rehabilitation robot in different motion states are obtained. The data are analyzed to verify the correctness of the data, which provides a theoretical basis for the next step of the physical prototype fabrication and the selection of the actuator.